Perbandingan efektivitas abate dengan bubuk biji pepaya (carica papaya linnaeus) dalam menghambat larva Nyamuk Aedes Aegypti - Pramawati, Anita; Kafit, M.; Martha, Elsusi; Candra, Rozie Zurfie (Universitas Widya Gama Mahakam Samarinda, 2020)
Background: Mosquito-borne diseases such as DHF (Dengue Hemorrhagic Fever) are still a public health problem. The purpose of this study was to compare the effectiveness of abate with papaya seed powder (carica papaya linnaeus) in inhibiting Aedes aegypti larvae.Method: The method in this research is experimental research or experiment (experimental research). The type of research used in this research is True - experiment with Posttest Only Control Design research design. The samples in this study were 3rd instar Aedes aegypti larvae.Results: Comparison of the effectiveness of Abate with Papaya Seed Powder (Carica papaya Linnaeus) in inhibiting Aedes aegypti mosquito larvae, namely the average mortality rate of larvae at abate was 6,8000 with a standard intersection of 7,55425, while the average mortality rate of larvae of papaya seeds (Carica Papaya Linnaeus) was 4.7000 with standard intersection 7.48406. with the independent test, it was found that the significance was p = 0.540 (p = <0.05), meaning that there was no significant difference between the mortality of larvae caused by abate and papaya seed powder.Conclusion: It is expected that people will care more about the environment in which they live by always maintaining cleanliness both inside and outside the home